Evaluation of the Clean Water Program Policy in Bau Village, Soyo Jaya District, North Morowali Regency - Mohammad Rusli Syuaib (Universitas Muhammadiyah Palu, 2023)
Water is an abundant natural resource. Which is a basic need for all human activities, including domestic needs such as drinking, cooking, bathing, as well as industrial, commercial, agricultural, medical, marine and other needs. Therefore, water is very useful and important for life on earth. In the research the author used a research approach, the research method the author used was the survey method. The survey method dissects and identifies problems and obtains justification for the ongoing situation. This research shows effectiveness, which shows that the goals that have been set have not been achieved considering that the community's need for clean water has not been met. Efficiency, seen from the efforts made by the Bau Village Government together with Clean Water Officers in maintaining clean water facilities, is quite good. Adequacy, seen from the community's response, shows that some of them do not feel their needs for clean water are met. Alignment, shows that it is quite good at providing justice to society. Responsiveness, it can be seen that the community is not satisfied with the clean water program, however all community complaints are well received by the Bau Village Government and Clean Water Officers. Accuracy shows that this clean water program is quite appropriate in overcoming clean water problems in Bau Village.